Detection of large expansions in myotonic dystrophy type 1 using triplet primed PCR - Singh, Susmita; Zhang, Amy; Dlouhy, Stephen; Bai, Shaochun (Frontiers in Genetics, 2014)
Myotonic dystrophy type 1 (DM1) is an autosomal dominant neuromuscular disease caused by expansion of a CTG trinucleotide repeat in the DMPK gene. Methodology for genetic testing of DM1 is currently not optimal, in particular for the early-onset patients in pediatric populations where large expanded (CTG)n alleles are usually common. Individuals who are homozygous for a normal allele and individuals who are heterozygous for one normal and one large expanded allele are indistinguishable by conventional PCR, as both generate a single product of the normal allele. Thus, reflex Southern blot has often been needed to distinguish these cases. With the aim to decrease the need for reflex Southern blot tests, a novel, single-tube CTG repeat primed PCR technology was designed to distinguish the true homozygous patients from the individuals whose large alleles are missed by conventional PCR. The method utilizes two gene-specific primers that flank the triplet repeat region and a third primer set complementary to the repeated region to detect the large alleles. Compared to traditional PCR, this novel Triplet-repeat Primed PCR can detect the presence of large expanded alleles with demonstrating a ladder pattern. Using this single-step protocol, 45 specimens were tested. The alleles with sizes ≤ 85 repeats were determined by the gene specific primers. 13 abnormal alleles, which missed by the conventional PCR, were successfully detected by the Triplet-repeat Primed PCR. All the abnormal alleles were confirmed and measured by Southern Blot analysis. In summary, optimized TP-PCR can accurately detect the presence of the large expanded alleles. With the ability to distinguish the true homozygous patients from the false negative homozygous individuals, the application of the optimized TP-PCR can significantly reduce the need of Southern Blot tests.